The Relevance of Credibility Excess in a Proportional View of Epistemic Injustice: Differential Epistemic Authority and the Social Imaginary - Medina, José (Social Epistemology, 2011)
This paper defends a contextualist approach to epistemic injustice according to which instances of such injustice should be looked at as temporally extended phenomena (having developmental and historical trajectories) and socially extended phenomena (being rooted in patterns of social relations). Within this contextualist framework, credibility excesses appear as a form of undeserved epistemic privilege that is crucially relevant for matters of testimonial justice. While drawing on Miranda Fricker's proportional view of epistemic justice, I take issue with its lack of attention to the role that credibility excesses play in testimonial injustices. I depart from Fricker's view of the relation between credibility excesses and credibility deficits, and I offer an alternative account of the contributions that undeserved epistemic privileges make to epistemic injustices. Then, through the detailed analysis of To kill a mockingbird, I elucidate the crucial role played by the social imaginary in creating and sustaining epistemic injustices, developing an analysis of the kind of social blindness produced by an oppressive social imaginary that establishes unjust patterns of credibility excesses and deficits.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; droit; fem9000; histoire et politique; injustices épistémiques; inégalités; justice sociale; philosophie; privilèges; privilèges de crédibilité; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques; éthique

Mettre l'amitié au premier plan : passés et futurs féministes - Roseneil, Sasha (Nouvelles Questions Féministes, 2011)
L'amitié est un champ d'études peu exploré et cependant d'importance vitale pour les études genre et féministes. En revisitant l'histoire des écrits féministes sur les amitiés entre femmes, l'article explore l'importance qui est donnée à l'amitié par les premières générations de féministes tout au long du XXe siècle. En se concentrant sur les considérations polémiques, théoriques et empiriques à l'égard de l'amitié, l'article suggère que l'amitié a été historiquement fondamentale pour les politiques, les identités et les communautés féministes. Il conclut par un argument en faveur de la place centrale de l'amitié - avec le même sexe, hommes et femmes, mais aussi entre les sexes - dans les programmes de recherche féministes, aujourd'hui et dans l'avenir. Le prisme de l'amitié conduit à une remise en question radicale de l'hétéronormativité des sciences sociales, et attire notre attention sur les façons dont la vie intime a été reconfigurée au début du XXIe siècle.
https://www.jstor.org/stable/41346017 Traduction de : Sasha Roseneil (2006). « Foregrounding Friendship : Feminist Pasts, Feminist Futures ». In Kathy Davis, Mary Evans & Judith Lorber (Éds) Handbook of Gender Women’s Studies, (pp. 322-341). Londres : SAGE Publications.
Keywords: 1900-1999; amitié; approches et analyses; care; cours; cycles supérieurs; discipline; fem7000; genre; histoire de l'art; histoire et politique; hétéronormativité; hétérosexisme; intimité; lesbianisme; littérature française; littérature lesbienne; phi2030; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques; écriture des femmes*; études littéraires